Mongol sudlalyn ögüülėlüüd = Mongġol sudulul-un ögülelge-nügüd = Essays on mongol studies = Raboty po mongolvedeniju - Menes, Gochoogijn 1958-2010 ("Mönhijn Üsėg" HHK, 2015)
A collection of papers by Mongolian scholar, G. Mėnės (1958-2010)
Keywords: Secret history of the Mongols; Excavations (Archaeology) / Mongolia; Mongols / History / To 1500; Mongols / Histoire / Jusqu'à 1500; Antiquities; Excavations (Archaeology); Mongols; Archäologie; Mongolia / Antiquities; Mongolia; Mongolei